PENGARUH KECERDASAN INTELEKTUAL (IQ), KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) TERHADAP PERILAKU SOSIAL SISWA SMPN 1 KADUGEDE KABUPATEN KUNINGAN - Tintin Hartini (Oasis : Jurnal Ilmiah Kajian Islam, 2017)
The object this researchs are: (1) to find influence of intellectual intelligence for social behavior students (2) to find influence of emotional intelligence for social behavior students (3) to find influence of spiritual intelligence for social behavior students (4) to evidence influence of intellectual intelligence, emotional intelligence and spiritual intelligence for social behavior students of SMPN 1 Kadugede district Kuningan.This research use quantitative method where the writer present the data base on questionersin-the field. The analysis technique the data use regrissim, determination, and dereble regression. The data collected processing to see, analysis, and description base on the problem and to object research.Base on this research the can be concluded that there are : (1) there is influence of intellectual intelligence (IQ) with social behavior students the way of significant and pattern direction is 25,6% and the research include of catagery enough strong (2) there is influence of emotional intelligence (EQ) with social behavior students the way of significant and the pattern direction is 46,7% and the research in clude of category enough strong (3) there is influence of spiritual intelligence (SQ) with social behavior students the way of significant and the pattern direction is 45,6% and the research in clude of category enough strong (4) there are influence of intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) with social behavior students are significant and there is relation direction is 56,5% and include of category strong.Key words : Intelectual Intelligence (IQ), Emotional Intelligence (EQ), Spiritual Intelligence (SQ) and Social Behavior.